Chemical Composition of Essential Oils of Achillea teretifolia Willd. and A. millefolium L. subsp. millefolium Growing in Turkey - Kocak, Alpaslan; Bagci, Eyup; Bakoglu, Adil (Asian Journal of Chemistry, 2010)
The chemical composition of the essential oils of dried aerial parts of Achillea teretifolia and A. millefolium subsp. millefolium were analyzed by GC and GC-MS. Sixty seven and 57 components were identified representing 95.58 and 91.41 % of the oils, respectively. 3-Cyclohexen- 1-one (21.61 %), linalool (14.32 %), 1,8-cineole (12.71 %), chrysanthe-none (8.55 %), transchrysanthenol (7.83 %) and δ-cadinene (4.04 %) were found to be the major components in A. teretifolia while δ-cadinene (19.03 %), limonene oxide (10.13 %), alloaromadendrene (6.37 %), caryophyllene oxide (5.71 %) and trans-caryophyllene (4.89 %) were found as major constituents in A. millefolium subsp. millefolium.